2014
DOI: 10.3892/etm.2014.1989
|View full text |Cite
|
Sign up to set email alerts
|

Significance of hypoxia-inducible factor-1α expression with atrial fibrosis in rats induced with isoproterenol

Abstract: Atrial interstitial fibrosis plays a dual role in inducing and maintaining atrial fibrillation (AF). Hypoxia-inducible factor-1α (HIF-1α) has been reported as closely associated with renal, liver and pulmonary fibrosis diseases. However, whether HIF-1α is involved in myocardial fibrosis, and the associations between HIF-1α, transforming growth factor-β1 (TGF-β1) and matrix metalloproteinase-9 (MMP-9) remain unknown. Therefore, this area warrants studying for the significance of AF diagnosis and treatment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
0
20
0
2
Order By: Relevance
“…Previous studies have shown that the greater vulnerability of the atrium for re-entrant arrhythmias by hypoxia is based on the combination of a moderate shortening of the wavelength and an increase in homogeneity in the conduction of premature wavefronts 18,22. Other groups have shown that MMP-9 expression and upregulation of HIF-1a/VEGF increase in fibrillating atria, which may contribute to the atrial structural remodeling seen in these patients 2325. On the other hand, hypercapnia produces a marked and uniform increase in atrial refractoriness and a significant slowing in atrial conduction 22.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the greater vulnerability of the atrium for re-entrant arrhythmias by hypoxia is based on the combination of a moderate shortening of the wavelength and an increase in homogeneity in the conduction of premature wavefronts 18,22. Other groups have shown that MMP-9 expression and upregulation of HIF-1a/VEGF increase in fibrillating atria, which may contribute to the atrial structural remodeling seen in these patients 2325. On the other hand, hypercapnia produces a marked and uniform increase in atrial refractoriness and a significant slowing in atrial conduction 22.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ISO can promote the expression of HIF-1α in a variety of cells, which was independent of hypoxia-like environment. In our study [46][47][48], we found that HIF-1a mediated the effect of ISO on osteoblasts to enhance the secretion of CXCL12, indicating that HIF-1a signaling of osteoblasts may mediate prostate cancer bone metastasis in response to sympathetic activation. Further studies are needed to explore the mechanism of ISO-induced HIF-1α expression in osteoblasts.…”
Section: Osteoblasts Triggered By Iso Promote Migration and Invasion mentioning
confidence: 59%
“…Previous studies also showed that the increase in HIF-1α gene expression in the myocardium may be involved in structural changes in the myocardium, including atrial fibrosis [ 6 ]. In isoproterenol-treated rats, Su et al showed positive correlation of HIF-1α expression with the extent of myocardial fibrosis (collagen volume fraction index), which implies that HIF-1α can facilitate the expression of matrix metalloproteinase-9 (MMP-9) and TGF-β1 and thus, induce atrial fibrosis [ 7 ]. In our study, hypoxia significantly upregulated HIF-1α and profibrotic proteins expression in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that HIF-1 plays a role in the cardiorespiratory response to hypoxia [ 5 ]. Atrial hypoxia and the HIF pathway have been implicated in structural changes of the atria, such as cardiac fibrosis, that may lead to the development of AF [ 6 , 7 ]. It has been reported that HIF-1α gene expression increases transiently in parallel with fibrogenesis in atrial myocardium during the early response of cardiomyocytes to AF [ 6 ].…”
Section: Introductionmentioning
confidence: 99%